Eco-enzyme from Organic Waste (Fruit and Rhizome Waste) Fermentation: Eco-Enzyme Dari Fermentasi Sampah Organik (Sampah Buah Dan Rimpang) - Piyantina Rukmini; Dewi Astuti Herawati (Program Studi S1 Teknik Kimia, Fakultas Teknik, Universitas Setia Budi, 2023)
This research aims to determine characteristics of ecoenzyme made from organic matters sweet orange peels, ginger (Zingiber ofcinale Rosc), turmeric (Curcuma Longa), fart ((Kaempferia galangal), galangal (Alpinia galanga), molasses, and water. Organic materials with a certain composition are mixed with molasses and water in a ratio of 3 : 1 : 10 in 7 bioreactors. Fermentation was carried out for 90 days (3 months) and observed changes in pH, color and odor. The results showed that the pH of the seven bioreactors showed the number 4. The color of the eco-enzyme liquid from the seven reactors showed a change in the appearance of the color of the liquid to become more brown than the initial fermentation and cloudy. The eco-enzyme liquid from the rhizome is light brown in color. Changes in the smell of the seven eco-enzyme liquids in the bioreactor also show changes, which are increasingly acidic in the second month and are typical of the organic matter they come from. During the eco-enzyme fermentation accompanied by the growth of microbes or fungi. AbstrakPenelitian ini bertujuan untuk mengetahui karakteristik eco-enzyme yang berbahan organik kulit buah jeruk manis (Citrus sinensis) dan beberapa jenis rimpang seperti jahe (Zingiber ofcinale Rosc), Kunyit (Curcuma Longa), kencur (Kaempferia galangal), Laos (Alpinia galanga), molase, dan air. Bahan organik dengan komposisi tertentu dicampur dengan molase dan air dengan perbandingan 3 : 1 : 10 di dalam 7 buah bioreaktor. Fermentasi dilakukan selama 90 hari (3 bulan) dan diamatii perubahan pH, warna, dan bau. Hasil penelitian menunjukkan bahwa pH dari ketujuh bioreaktor menunjukkan angka 4. Warna cairan eco-enzyme dari ketujuh buah reaktor menunjukkan ada perubahan kenampakan warna cairan menjadi lebih coklat daripada awal fermentasi dan keruh. Cairan eco-enzyme dari rimpang berwarna coklat muda terang. Perubahan bau dari ketujuh cairan eco-enyzme dalam bioreaktor juga menunjukkan perubahan, yaitu semakin asam padai bulan kedua dan khas bahan organik asalnya.Selama fermentasi eco-enzyme disertai dengan tumbuhnya mikroba atau jamur.